2020
DOI: 10.1099/mgen.0.000402
|View full text |Cite
|
Sign up to set email alerts
|

The compact genome of Giardia muris reveals important steps in the evolution of intestinal protozoan parasites

Abstract: Diplomonad parasites of the genus Giardia have adapted to colonizing different hosts, most notably the intestinal tract of mammals. The human-pathogenic Giardia species, Giardia intestinalis, has been extensively studied at the genome and gene expression level, but no such information is available for other Giardia species. Comparative data would be particularly valuable for Giardia … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 94 publications
2
32
0
Order By: Relevance
“…The high contiguity of the assembly is underscored by the large number of transcripts mapped to single contigs (90.2%), and since the proteins encoded by transcripts were consistently found in the predicted proteome, the latter is also considered to be of high quality. We also conducted BUSCO analyses, with the foreknowledge that genomic streamlining typical in Metamonada has led to the loss of many conserved proteins 17,24,25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high contiguity of the assembly is underscored by the large number of transcripts mapped to single contigs (90.2%), and since the proteins encoded by transcripts were consistently found in the predicted proteome, the latter is also considered to be of high quality. We also conducted BUSCO analyses, with the foreknowledge that genomic streamlining typical in Metamonada has led to the loss of many conserved proteins 17,24,25 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite using a phylogeny-guided search with the Eukaryota database, a more comprehensive database than the protist BUSCO database, a remarkably large number of BUSCO proteins were inconsistently present in Metamonada. This is not surprising, as the clade harbors a very diverse group of taxa with varied lifestyles and many have undergone genome streamlining 9,10,[23][24][25] , and the BUSCO databases are expected to be more accurate with greater taxonomic proximity to the studied genome 1,26,27 . While it might be tempting to suggest the 101 BUSCO proteins that are shared by all metamonads be used to evaluate genome completion in the clade, the overwhelming evidence of differential genome streamlining strongly indicates that databases should be lineage specific (e.g., Carpediemonas, Giardia, etc).…”
Section: C1 Busco Incompletenessmentioning
confidence: 99%
“… Giardia intestinalis WB lost the ability to degrade arginine to l -ornithine and urea, making the deimination of arginine to l -citrulline the only option to degrade this amino acid. Giardia intestinalis GS B shared the ability to degrade arginine through two different pathways with G. muris ( 30 ). On the other hand, G. intestinalis GS B lost the synthesis of glycine from glyoxylate.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of those pathways suggested that G. muris is highly dependent on a supply of nucleosides and nucleotides, especially purines, from the environment within the host. On the other hand, G. muris can synthesize coenzyme A de novo ( 30 ). Our analysis suggested that the genes responsible for the synthesis of coenzyme A in G. muris were acquired independently in the lineages leading to G. muris and S. salmonicida ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation